Qualitative research skills acquisition within social work doctoral education using project-based learning. (September 2020) - Yang, Fan; Maynard, Quentin R; Young, Sarah R; Kenney, Jennifer L; Barber, Brad; Boltz, Laura; Womack, Bethany; Young, Teresa L; Nelson-Gardell, Debra; Zhang, Xiangda
The future of social work research relies on the intellect and competence of current doctoral students. These future scholars who receive doctoral education that values qualitative inquiry will create a system where qualitative research traditions receive the same privilege as quantitative research traditions. Project-based learning provides learning opportunities that can challenge assumptions about what academia considers "real" research. This descriptive qualitative study explored key attributes of using project-based learning within two consecutive social work doctoral courses to encourage qualitative research skill development. Students and instructors participated in ideawriting and focus groups to assess the usefulness of PBL within these courses. The findings suggested that PBL may be useful for deepening knowledge about qualitative inquiry and reducing epistemological unconsciousness.